Oxidative stress – Complex pathological issues concerning the hallmark of cardiovascular and metabolic disorders - Rotariu, Dragos; Babes, Emilia Elena; Tit, Delia Mirela; Moisi, Madalina; Bustea, Cristiana; Stoicescu, Manuela; Radu, Andrei-Flavius; Vesa, Cosmin Mihai; Behl, Tapan; Bungau, Alexa Florina; Bungau, Simona Gabriela (Biomedicine & pharmacotherapy, 2022)
Oxidative stress is a complex biological process characterized by the excessive production of reactive oxygen species (ROS) that act as destroyers of the REDOX balance in the body and, implicitly, inducing oxidative damage. All the metabolisms are impaired in oxidative stress and even nucleic acid balance is influenced. ROS will promote structural changes of the tissues and organs due to interaction with proteins and phospholipids. The constellation of the cardiovascular risk factors (CVRFs) will usually develop in subjects with predisposition to cardiac disorders. Oxidative stress is usually related with hypertension (HTN), diabetes mellitus (DM), obesity and cardiovascular diseases (CVDs) like coronary artery disease (CAD), cardiomyopathy or heart failure (HF), that can develop in subjects with the above-mentioned diseases. Elements describing the complex relationship between CVD and oxidative stress should be properly explored and described because prevention may be the optimal approach. Our paper aims to expose in detail the complex physiopathology of oxidative stress in CVD occurrence and novelties regarding the phenomenon. Biomarkers assessing oxidative stress or therapy targeting specific pathways represent a major progress that actually change the outcome of subjects with CVD. New antioxidants therapy specific for each CVD represents a captivating and interesting future perspective with tremendous benefits on subject’s outcome. [Display omitted] •ROS promote structural changes of the tissues/organs due to the interaction with proteins and phospholipids.•Oxidative stress – related with hypertension, diabetes mellitus, obesity, and cardiovascular diseases•New antioxidants therapy for CVDs – future perspective with high benefits on subject’s outcome.